ANALYSIS OF THE EXISTENCE OF THE RIGHT TO REMAIN SILENT PRINCIPLE FOR THE SUSPECT AND THE DEFENDANT BASED ON THE BOOK OF CRIMINAL PROCEDURE AND PROJECTIONS IN CRIMINAL PROCESS - Russiana Ika Puspitasari (Jurnal Multidisiplin Sahombu, 2021)
This legal research aims to determine: (1) the existence of the guarantee of the right to remain silent for suspects and defendants in the criminal case process according to the Criminal Procedure Code, and (2) to find out the importance of the right to remain silent principle and future projections in the criminal case process. . The research method used in writing this law is a prescriptive normative research. The type of data used is secondary data. The secondary data sources used include primary legal materials, secondary legal materials, and tertiary legal materials. The data collection technique used is a literature study in the form of secondary data collection, by searching for data from books, documents, archives and legislation related to the object of research. The presiding judge of the trial recommended to answer and after that the examination was continued. And projections according to positive law in Indonesia, the principle of the right to remain silent KUHAP does not recognize the existence of the right to remain silent principle, the Criminal Procedure Code only mentions the issue of the right to remain silent principle in the examination stage at the trial, while in the pre-trial stage there are no arrangements .